Conductive wave-absorbing composite material and preparation method thereof

By applying water-based slurry on PET tape and attaching conductive cloth, the problems of poor structural stability and poor absorption properties of conductive wave absorbing composite materials are solved, and better conductivity and absorption properties are achieved. The preparation process is simplified.

CN119489594APending Publication Date: 2025-02-21CHONGQING HFC ELECTRONIC NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411643589.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing conductive wave absorbing composite materials have poor structural stability and poor absorption and conductivity.

Method used

The PET tape is coated with a scraper coating method, and a conductive cloth is directly attached before drying to form a three-layer conductive wave-absorbing composite material.

Benefits of technology

The structural stability, absorbency and conductivity of the conductive wave-absorbing composite material are improved, and the preparation process is simplified and production efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489594A_ABST
    Figure CN119489594A_ABST
Patent Text Reader

Abstract

The invention discloses a conductive wave-absorbing composite material and a preparation method thereof, and belongs to the technical field of electromagnetic shielding. Coating the water-based slurry for forming the wave-absorbing layer on a PET (Polyethylene Terephthalate) adhesive tape by adopting a blade coating method, and forming a slurry layer on the PET adhesive tape; wherein the slurry is prepared from 100 to 200 parts of water, 60 to 90 parts of magnetic powder, 0.3 to 2 parts of a dispersing agent, 0 to 3 parts of a wetting agent, 0.1 to 2 parts of a defoaming agent, 10 to 30 parts of a binding agent, 0 to 20 parts of a surface treating agent, a pH (Potential of Hydrogen) regulator and 5 to 30 parts of a thickening agent. Before the slurry layer is dried and cured to form the wave-absorbing layer, the conductive cloth is directly attached to the slurry layer, and then the slurry layer and the wave-absorbing layer are dried together, so that the slurry layer is cured to form the wave-absorbing layer, and the conductive wave-absorbing composite material with good structural stability, conductivity and wave-absorbing property can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electromagnetic shielding, and in particular to a conductive wave-absorbing composite material and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology and the electronics industry, various digital and high-frequency electronic devices are widely used in daily life and industrial production, bringing convenience to human life. However, these devices will generate a large number of electromagnetic waves of different wavelengths during operation. These electromagnetic waves may not only interfere with each other and affect the normal operation of the equipment, but also cause harm to human health and the environment. Therefore, wave absorbing technology came into being, with the aim of reducing or eliminating the interference and harm of electromagnetic waves to equipment, human body and environment.

[0003] Conductive cloth absorbing and shielding material is a composite material that combines conductivity and absorbing properties. It has important application value and development prospects in the field of absorbing waves.

[0004] However, the current conductive cloth wave-absorbing and shielding materials have poor structural stability, and their wave-absorbing and conductivity need to be further improved. Summary of the invention

[0005] Based on the above-mentioned deficiencies, the present application provides a conductive absorbing composite material and a preparation method thereof to improve the problems of poor structural stability, poor absorption and conductivity of the conductive absorbing composite material in the related art.

[0006] This application is implemented as follows:

[0007] In a first aspect, an example of the present application provides a method for preparing a conductive wave-absorbing composite material, wherein the conductive wave-absorbing composite material comprises a PET tape, a wave-absorbing layer, and a conductive cloth stacked in sequence. The preparation method comprises:

[0008] The slurry for forming the wave absorbing layer is coated on the PET tape by a doctor blade coating method to form a slurry layer on the PET tape; the conductive cloth is attached to the slurry layer, dried, and the slurry layer is solidified to form the wave absorbing layer, thereby obtaining a conductive wave absorbing composite material. The slurry includes, by weight: 100-200 parts of water, 60-90 parts of magnetic powder, 0.3-2 parts of dispersant, 0-3 parts of wetting agent, 0.1-2 parts of defoaming agent, 10-30 parts of binder, 0-20 parts of surface treatment agent, pH regulator and 5-30 parts of thickener.

[0009] In the above implementation process, when preparing a three-layer stacked conductive absorbing composite material, a doctor blade coating method is used to coat the aqueous slurry with the above content on a PET tape, and before the coated slurry layer is dried to form an absorbing layer, a conductive cloth is directly attached to the slurry layer, and then the attached conductive cloth and the slurry layer are dried together, so that a conductive absorbing composite material with good structural stability, absorbency and conductivity can be obtained.

[0010] In combination with the first aspect, in an optional implementation manner of the present application, the viscosity of the slurry is 4000-10000 Pa.s; optionally, the conductive cloth is selected from copper conductive cloth.

[0011] In the above implementation process, a scraper coating method is used to apply the absorbing layer slurry with a viscosity of 4000-10000 Pa.s on the PET tape, which can facilitate the direct attachment of the conductive cloth on the slurry layer, so as to obtain a firmly bonded conductive absorbing composite material after subsequent drying. The copper conductive cloth has good conductivity, and the absorbing layer is tightly attached to the copper conductive cloth, which can further improve the conductivity of the conductive absorbing composite material. The copper conductive cloth has good flexibility, and the conductive absorbing composite material obtained after compounding has excellent flexibility, can be bent and folded freely, and the absorbing layer is firmly bonded to the copper conductive cloth. When the conductive absorbing composite material is bent and folded, the absorbing layer is not easily separated from the conductive cloth, which can improve the absorbing property of the conductive absorbing composite material.

[0012] In combination with the first aspect, in an optional embodiment of the present application, during blade coating, the height of the blade is 0.3-1 mm, the drying temperature is 45-200° C., and the drying time is 15-30 min.

[0013] In the above implementation process, the slurry is scraped onto the PET tape at a scraper height of 0.3-1 mm, which makes it easy to attach the conductive cloth to the slurry layer, and then dried at a temperature of 45-200° C. for 15-30 minutes to obtain a firmly bonded conductive absorbing composite material.

[0014] In combination with the first aspect, in an optional embodiment of the present application, the slurry includes: 100-200 parts of water, 60-90 parts of magnetic powder, 0.3-2 parts of dispersant, 0-3 parts of wetting agent, 0.1-2 parts of defoaming agent, 10-30 parts of binder, 0-20 parts of surface treatment agent, pH adjuster and 5-30 parts of thickener.

[0015] In the above implementation process, the slurry with the above components and contents is coated on the PET tape, compounded with the conductive cloth and dried, so as to obtain a conductive absorbing composite material with good structural stability and absorbency, and also improve the flexibility and wear resistance of the conductive absorbing composite material.

[0016] Furthermore, the use of the above-mentioned aqueous slurry to prepare the absorbing layer can reduce environmental pollution and improve environmental protection compared to the organic solvent in the traditional slurry because water is used as the solvent.

[0017] In combination with the first aspect, in an optional embodiment of the present application, the slurry further includes 0.1-2 parts of a preservative and mildew preventer.

[0018] Optionally, the preservative and mildew preventer is selected from at least one of isothiazolinones, phenylimidazoles, iodopropargyls or dithiocarbamates.

[0019] In the above implementation process, adding 0.1-2 parts of antiseptic and mildew inhibitor into the slurry can also improve the corrosion resistance of the conductive wave-absorbing composite material and increase the service life of the conductive wave-absorbing composite material.

[0020] In combination with the first aspect, in an optional embodiment of the present application, the magnetic powder is selected from at least one of nickel zinc ferrite powder, zinc manganese ferrite powder, iron silicon aluminum soft magnetic powder, iron silicon chromium soft magnetic powder, iron nickel molybdenum powder or carbonyl iron powder.

[0021] Optionally, the magnetic powder is selected from at least one of sendustine-aluminum soft magnetic powder and iron-silicon-chromium soft magnetic powder.

[0022] In the above implementation process, the wave absorption property of the conductive wave absorbing composite material can be improved by using magnetic powders such as nickel zinc ferrite powder, zinc manganese ferrite powder, iron silicon aluminum soft magnetic powder, iron silicon chromium soft magnetic powder, iron nickel molybdenum powder or carbonyl iron powder.

[0023] In combination with the first aspect, in an optional embodiment of the present application, the dispersant is selected from one of a cationic dispersant, a nonionic dispersant and a polymer dispersant; and / or the wetting agent is selected from a silicone wetting agent; and / or the defoaming agent is selected from at least one of a mineral oil defoaming agent, a silicone defoaming agent, a low-alcohol defoaming agent or a lipid defoaming agent.

[0024] In combination with the first aspect, in an optional embodiment of the present application, the binder is selected from at least one of polyurethane, acrylic or UV resin; and / or the surface treatment agent is selected from one of polyvinyl pyrrolidone or γ-aminopropyltriethoxysilane; and / or the thickener is selected from one of polyacrylate alkali swelling emulsion, polyurethane thickener, hydrophobically modified non-polyurethane thickener or inorganic thickener; and / or the pH adjuster adjusts the pH of the slurry to 8-9; optionally, the pH adjuster is selected from ammonia water.

[0025] In combination with the first aspect, in an optional embodiment of the present application, the method for preparing the slurry includes:

[0026] The weighed water and magnetic powder are stirred evenly to wet the magnetic powder; a dispersant, a wetting agent, a defoaming agent, a binder, a surface treatment agent, a pH adjuster and a thickener are added in sequence and stirred to mix.

[0027] In the above implementation process, when preparing the aqueous slurry for forming the wave absorbing layer, the weighed magnetic powder is first mixed with water to make the magnetic powder soaked, and then the dispersant and wetting agent are added in sequence and stirred to make the magnetic powder evenly dispersed and reduce the probability of magnetic powder agglomeration; then the weighed defoaming agent is added and stirred to disperse evenly to reduce the bubbles in the slurry; then the binder and surface treatment agent are added in sequence and stirred evenly, and then an alkaline pH adjuster is added to adjust the pH to 8-9, and finally a thickener is added and stirred evenly to make the viscosity of the slurry 4000-10000Pa.s, so as to facilitate subsequent scraper coating and conductive sheet attachment.

[0028] In a second aspect, an example of the present application provides a conductive and wave-absorbing composite material, which is prepared according to the preparation method provided in the first aspect.

[0029] In the above implementation process, the conductive absorbing composite material prepared by the preparation method provided by the first aspect of the present application adopts a doctor blade coating method in the preparation process, wherein the aqueous slurry used to form the absorbing layer is coated on the PET tape, and after the slurry layer is formed on the PET tape, the conductive cloth is directly attached to the slurry layer, and then dried together to cure the slurry layer to form the absorbing layer, thereby improving the bonding stability between the absorbing layer and the conductive cloth, and improving the conductivity and absorbing performance of the conductive absorbing composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0031] Figure 1 A schematic plan view of a conductive and wave-absorbing composite material provided as an example of this application;

[0032] Figure 2 A flow chart of the preparation process of the conductive and absorbent composite material provided as an example in this application.

[0033] Icon: 100-conductive and absorbing composite material; 101-PET tape; 102-absorbing layer; 103-conductive cloth. DETAILED DESCRIPTION

[0034] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0035] Conductive cloth absorbing shielding material is a composite material that combines conductivity and absorbing properties, and has important application value and development prospects in the field of absorbing. However, the current conductive cloth absorbing shielding material has poor structural stability, and its absorbing and conductive properties need to be further improved. In addition, the current preparation process of conductive cloth absorbing shielding material is complicated, the operation is cumbersome, and the production efficiency is low.

[0036] Therefore, the present application example provides a conductive absorbing composite material and a preparation method thereof to improve the problems of complex preparation process, poor structural stability, poor conductivity and absorbing performance of the conductive absorbing composite material. In order to make the purpose, technical solution and advantages of the embodiment of the present application clearer, the technical solution in the embodiment of the present application will be clearly and completely described below in conjunction with the drawings in the embodiment of the present application.

[0037] See also Figure 1 The conductive wave-absorbing composite material 100 provided in the example of the present application includes a PET tape 101, a wave-absorbing layer 102 and a conductive cloth 103 which are stacked in sequence.

[0038] See also Figure 2 The method for preparing the conductive wave-absorbing composite material provided in the example of the present application includes:

[0039] S1. Obtain a slurry for forming the wave absorbing layer 102. The slurry includes, by weight: 100-200 parts of water, 60-90 parts of magnetic powder, 0.3-2 parts of dispersant, 0-3 parts of wetting agent, 0.1-2 parts of defoaming agent, 10-30 parts of binder, 0-20 parts of surface treatment agent, pH adjuster and 5-30 parts of thickener.

[0040] S2 . Apply the slurry for forming the absorbing layer 102 onto the PET tape 101 by using a doctor blade coating method, so as to form a slurry layer on the PET tape 101 .

[0041] S3 , attaching the conductive cloth 103 to the slurry layer, drying, and solidifying the slurry layer to form the absorbing layer 102 , thereby obtaining the conductive absorbing composite material 100 .

[0042] When the three-layer composite conductive absorbing composite material 100 is prepared by the above method, the aqueous slurry is coated on the PET tape 101 by a doctor blade coating method. Before the coated slurry layer is dried to form the absorbing layer 102, the conductive cloth 103 is directly attached to the slurry layer. Then, the attached conductive cloth 103, the slurry layer and the PET tape 101 are sent to an oven for drying. The slurry layer can be in-situ cured between the conductive cloth 103 and the PET tape 101 to form the absorbing layer 102, so that the bonding between the absorbing layer 102 and the conductive cloth 103 is more firm, thereby increasing the structural stability, conductivity and absorbing performance of the conductive absorbing composite material 100.

[0043] In addition, in the preparation method provided by the example of the present application, the conductive cloth 103 is directly attached to the slurry layer after coating, and then dried together. Compared with the traditional preparation process of drying and curing the slurry layer after coating, rolling, unwinding, and attaching the conductive cloth 103 to the absorbing layer 102 through a back adhesive machine, the preparation method provided by the example of the present application does not need to form an adhesive layer between the conductive cloth 103 and the absorbing layer 102, and the preparation process is simpler, the preparation efficiency is higher, and the conductivity and absorbing performance of the conductive absorbing composite material 100 are better. In addition, if an adhesive layer is set between the conductive cloth 103 and the absorbing layer 102, the adhesive layer is easy to age and fall off, which affects the service life of the conductive absorbing composite material 100.

[0044] Furthermore, in the preparation method provided by the example of the present application, a doctor blade coating method is used to coat the aqueous slurry on the PET tape 101, and then the conductive cloth 103 is attached to the slurry layer, which can improve the coating property of the slurry and enable the dried and cured absorbing layer 102 to be firmly combined with the conductive cloth 103. If the slurry is directly coated on the conductive cloth 103, since the slurry is aqueous, it is easy to seep water during the slurry coating, which affects the coating quality and the structural stability of the conductive absorbing composite material 100.

[0045] In order to further improve the conductivity, wave absorption performance and structural stability of the conductive wave absorbing composite material 100, in step S1, the slurry includes, by weight, 100-200 parts of water, 60-90 parts of magnetic powder, 0.3-2 parts of dispersant, 0-3 parts of wetting agent, 0.1-2 parts of defoamer, 10-30 parts of binder, 0-20 parts of surface treatment agent, pH regulator and 5-30 parts of thickener. By using the slurry with the above ratio and combining it with the doctor blade coating process, the conductive cloth 103 is directly attached to the slurry layer after the slurry is coated, which can improve the wave absorption, flexibility and wear resistance of the conductive wave absorbing composite material 100 while improving the attachment stability.

[0046] Furthermore, in order to improve the corrosion resistance of the conductive and absorbing composite material 100, an antiseptic and antifungal agent may be added to the slurry provided in the example of the present application.

[0047] Furthermore, in order to improve the coating performance of the slurry and the absorbency, conductivity and structural stability of the conductive and absorbing composite material 100, the present application example also provides a method for preparing the slurry, including:

[0048] S11. Add water and magnetic powder into a clean batching bucket and stir for 10-20 minutes to fully wet the magnetic powder;

[0049] S12, add dispersant and wetting agent, and stir for 10-20 minutes to make the powder dispersed evenly;

[0050] S13, add defoamer and preservative and mildew preventer, mix, and stir for 10-20 minutes to disperse at high speed;

[0051] S14, add binder and stir for 10-20 minutes;

[0052] S15, adding a surface treatment agent;

[0053] S16, adding a pH regulator;

[0054] S17. Add thickener and stir to disperse.

[0055] Among them, in step S11, 100-200 parts of water and 60-90 parts of magnetic powder are stirred and dispersed, which can make the magnetic powder fully infiltrated, make the slurry components prepared subsequently dispersed evenly, reduce the probability of magnetic powder agglomeration, improve the bonding firmness of the magnetic powder in the absorbing layer 102 formed after blade coating, and improve the absorbency, conductivity and structural stability of the conductive absorbing composite material 100.

[0056] The present application does not limit the specific amounts of water and magnetic powder, and appropriate amounts can be selected within the above range.

[0057] Exemplarily, the amount of water can be selected from one of 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts or 200 parts, or a range between any two of them.

[0058] For example, the amount of magnetic powder can be selected from one of 60 parts, 70 parts, 80 parts or 90 parts, or a range between any two of them.

[0059] Furthermore, in some possible embodiments, the magnetic powder is selected from at least one of nickel-zinc ferrite powder, zinc-manganese ferrite powder, iron-silicon-aluminum soft magnetic powder, iron-silicon-chromium soft magnetic powder, iron-nickel-molybdenum powder or carbonyl iron powder.

[0060] Exemplarily, the magnetic powder can be selected from sendust soft magnetic powder.

[0061] Exemplarily, the magnetic powder can be selected from iron silicon chromium soft magnetic powder.

[0062] In step S12, after the magnetic powder is fully wetted, a dispersant and a wetting agent are added and stirred for 10-20 minutes, so that the magnetic powder can be dispersed more evenly and the probability of magnetic powder agglomeration can be reduced.

[0063] In some possible embodiments, the dispersant may be selected from one of a cationic dispersant, a nonionic dispersant and a polymer dispersant.

[0064] For example, the dispersant may be selected from at least one of BYK110, BASF 4401, cationic polyacrylamide, polyether dispersants, acrylate dispersants, and polyamide dispersants.

[0065] For example, the polymeric dispersant may be selected from AG-214, AG-313 or AG-738.

[0066] For example, the amount of the dispersant may be selected from one of 0.3 parts, 0.5 parts, 1 part, 1.3 parts, 2 parts, 2.5 parts or 3 parts, or a range between any two of them.

[0067] In some possible embodiments, the wetting agent may be selected from silicone-based wetting agents.

[0068] Exemplarily, the wetting agent may include at least one of SG-604, DE-100, or AKN-1070.

[0069] Exemplarily, the amount of the wetting agent may be selected from one of 0.5 parts, 1 part, 1.3 parts, 2 parts, 2.5 parts or 3 parts, or a range between any two of them.

[0070] Alternatively, no wetting agent may be added to the slurry.

[0071] In step S13 , adding a defoaming agent to the slurry can eliminate bubbles in the slurry. After coating by a doctor blade coating method, an absorbing layer 102 with high flatness can be obtained, which can further improve the structural stability of the conductive absorbing composite material 100 .

[0072] In some possible embodiments, the defoaming agent may be selected from at least one of a mineral oil defoaming agent, a silicone defoaming agent, a lower alcohol defoaming agent or a lipid defoaming agent.

[0073] Further, the amount of the defoaming agent can be selected from one of 0.1 parts, 0.5 parts, 1 part, 1.5 parts or 2 parts, or a range between any two of them.

[0074] In step S13, adding an antiseptic and antifungal agent to the slurry can improve the corrosion resistance of the prepared conductive and microwave-absorbing composite material 100 and increase its service life.

[0075] In some possible embodiments, the preservative and mildew preventer is selected from at least one of isothiazolinones, phenylimidazoles, iodopropargyls or dithiocarbamates.

[0076] Furthermore, the amount of the preservative and mildew preventer can be selected from one of 0.1 parts, 0.5 parts, 1 part, 1.5 parts or 2 parts, or a range between any two of them.

[0077] In step S14 , a binder is added to the slurry to make the magnetic powder in the obtained absorbing layer 102 more solid, reduce the probability of the magnetic powder falling off from the absorbing layer 102 , and improve the absorbing property of the conductive absorbing composite material 100 .

[0078] In some possible embodiments, the adhesive may be selected from at least one of polyurethane, acrylic acid or UV resin.

[0079] Exemplarily, the binder may be polyurethane emulsion; or, the binder may be acrylic emulsion; or, the binder may be UV resin emulsion.

[0080] In some possible embodiments, the amount of the binder may be selected from at least one of 10 parts, 15 parts, 20 parts, 25 parts, and 30 parts.

[0081] In step S15, the surface treatment agent may be selected from polyvinyl pyrrolidone or γ-aminopropyltriethoxysilane.

[0082] Further, the amount of the surface treatment agent can be selected from one of 0.5 parts, 1 part, 5 parts, 10 parts, 15 parts or 20 parts, or a range between any two of them.

[0083] Alternatively, step S15 may not be performed, and the surface treatment agent may not be added to the slurry.

[0084] In step S16, a pH adjuster may be added to the slurry to adjust the pH of the slurry to 8-9.

[0085] Exemplarily, the pH adjuster may be selected from aqueous ammonia.

[0086] In step S17, a thickener is added to the slurry, and the slurry is stirred and dispersed to adjust the viscosity of the slurry to 4000-10000 Pa.s.

[0087] For example, the viscosity of the slurry may be in the range of one or any two of 4000 Pa.s, 8000 Pa.s or 10000 Pa.s.

[0088] Exemplarily, the viscosity of the slurry can be adjusted to 5000 Pa.s-7000 Pa.s; or, the viscosity of the slurry can be adjusted to 7000 Pa.s-10000 Pa.s.

[0089] In some possible embodiments, the thickener may be selected from one of polyacrylate alkali swelling emulsion, polyurethane thickener, hydrophobically modified non-polyurethane thickener or inorganic thickener.

[0090] Exemplarily, the thickener may be selected from at least one of DN-60 and DN-935.

[0091] Exemplarily, the amount of the thickener can be selected from one of 5 parts, 10 parts, 15 parts, 20 parts, 25 parts or 30 parts, or a range between any two of them.

[0092] Exemplarily, the amount of thickener may be 5-10 parts; alternatively, the amount of thickener may be 10-15 parts; alternatively, the amount of thickener may be 15-30 parts.

[0093] In the above-mentioned slurry preparation method, the corresponding raw materials are added separately in steps. Compared with the traditional method of directly stirring and mixing all the raw materials, the dispersion efficiency and dispersion quality can be improved, and the probability of magnetic powder agglomeration can be reduced. When the conductive and absorbing composite material is subsequently prepared, the structural stability, conductivity and absorption of the conductive and absorbing composite material can be further improved.

[0094] In step S2 and step S3, the aqueous slurry for forming the absorbing layer 102 is coated on the PET tape 101 by a doctor blade coating method, so that a stable and uniform slurry layer can be formed on the PET tape 101, and after the conductive cloth 103 is attached and dried together, a stably combined conductive absorbing composite material 100 can be formed.

[0095] In step S2, when applying with a scraper, the height of the scraper is 0.3-1 mm.

[0096] Exemplarily, the height of the scraper may be set to be one of 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm, or a range between any two of them.

[0097] In step S3, the conductive sheet may be selected from a copper conductive sheet.

[0098] In step S3, the drying temperature is 45-200°C.

[0099] Exemplarily, the drying temperature is 45-150°C; or, the drying temperature is 80-120°C.

[0100] Furthermore, the present application example also provides a conductive wave-absorbing composite material 100 prepared according to the above preparation method. The conductive wave-absorbing composite material 100 prepared by the above method has good structural stability, conductivity, wave-absorbing property, corrosion resistance and wear resistance.

[0101] The conductive and wave-absorbing composite material of the present application is further described in detail below in conjunction with the embodiments.

[0102] Example 1

[0103] Embodiment 1 provides a conductive wave-absorbing composite material, and the preparation method thereof is as follows:

[0104] (1) Add 150 parts of water and 75 parts of magnetic powder into a clean mixing barrel and stir for 15 minutes to fully wet the magnetic powder. The magnetic powder is iron silicon chromium soft magnetic powder.

[0105] (2) Add 1 part of dispersant and 0.5 part of wetting agent into the mixing barrel of step (1), and stir for 10 minutes to evenly disperse the powder; wherein the dispersant is a polymer dispersant (AG-214, AG-313, AG-738 mixed); the wetting agent is a silicone wetting agent (SG-604, DE-100, AKN-1070 mixed).

[0106] (3) Add 0.5 parts of defoaming agent and 0.6 parts of preservative and mildew inhibitor into the batching barrel in step (2), mix, and stir for 20 minutes for high-speed dispersion; wherein the defoaming agent is mineral oil, and the preservative and mildew inhibitor is isothiazolinone.

[0107] (4) Add 15 parts of a binder into the mixing barrel in step (3) and stir for 20 minutes; wherein the binder is polyurethane;

[0108] (5) Add 3 parts of a surface treatment agent into the mixing barrel in step (4); wherein the surface treatment agent is polyvinyl pyrrolidone;

[0109] Add an appropriate amount of alkaline solution to adjust the solution pH to between 8 and 9. In this process, the alkaline solution is ammonia water.

[0110] (6) Add 10 parts of thickener to the batching barrel in step (5) to make the slurry viscosity value between 6000 and 10000 Pa.s to obtain a slurry; wherein the thickener is an alkali swelling emulsion (DN-60 and DN-935 mixed).

[0111] (7) The slurry of step (6) is coated on a PET tape, and then a copper conductive cloth is attached to the slurry coating, dried at 120° C. for 2 min, and rolled up to obtain a conductive and absorbing composite material. The height of the coating blade is 0.3 mm.

[0112] The specific process parameters of Example 1 are shown in Table 1.

[0113] Example 2

[0114] Example 2 provides a conductive wave-absorbing composite material, which is different from Example 1 in that the specific components of the slurry are different, as shown in Table 1. The slurry includes, by weight: 100 parts of water, 80 parts of sendust soft magnetic powder, 1.5 parts of polymer dispersant, 1.5 parts of organosilicon wetting agent, 0.5 parts of mineral oil defoamer, 0.6 parts of benzyl imidazole preservative and mildew preventer, 20 parts of acrylic acid, 3 parts of polyvinyl pyrrolidone, pH regulator and 10 parts of polyurethane thickener.

[0115] Comparative Example 1

[0116] Comparative Example 1 provides a conductive wave-absorbing composite material, which differs from Example 1 in that:

[0117] In step (7), the slurry obtained in step (6) is coated on a PET tape, dried at 120° C. for 2 minutes, and rolled up; then the dried roll is unrolled and attached to a copper conductive cloth on a backing machine to obtain a conductive absorbing composite material.

[0118] Comparative Example 2

[0119] Comparative Example 2 provides a conductive wave-absorbing composite material, which is different from Example 1 in that the specific components of the slurry are different, as shown in Table 1. The slurry includes, by weight: 90 parts of water, 100 parts of sendust soft magnetic powder, 3 parts of polymer dispersant, 2 parts of organosilicon wetting agent, 0.5 parts of mineral oil defoamer, 0.6 parts of benzyl imidazole preservative and mildew preventer, 30 parts of acrylic acid, 3 parts of polyvinyl pyrrolidone, pH regulator and 5 parts of polyurethane thickener.

[0120] Table 1

[0121]

[0122]

[0123] Test Case

[0124] The peeling force and conductivity of the conductive wave-absorbing composite materials provided in Example 1-2 and Comparative Example 1-2 were tested, and the test method was as follows:

[0125] (1) Peel force test: Peel force test is performed using a peel tester that can apply a constant peel force and accurately measure the mechanical parameters during the peeling process.

[0126] (2) Conductivity test: The four-probe method is used to contact the material to be tested with four probes, two of which are used to apply voltage and the other two are used to measure current. By measuring the relationship between current and voltage, the resistance of the material can be calculated.

[0127] (3) Magnetic permeability test: Use a magnetic permeability tester for testing. The test method refers to GB / T356902017 "Test method for weak magnetic relative permeability".

[0128] The test results are shown in Table 2.

[0129] Table 2

[0130]

[0131] Result analysis:

[0132] By comparing Examples 1-2 with Comparative Example 1, it can be seen that the peeling forces of Examples 1-2 are greater than those of Comparative Example 1, and the resistances are less than those of Comparative Example 1, indicating that in Example 1, the aqueous slurry provided in the examples of the present application is used, the slurry is coated on a PET tape, and then the copper conductive sheet is directly attached to the coated slurry layer, and then dried together to prepare a conductive absorbing composite material. Compared with Comparative Example 1, in which the slurry is coated on a PET tape, dried to form an absorbing layer, and then the copper conductive sheet is attached to the absorbing layer to prepare the conductive absorbing composite material, the structural stability and magnetic permeability of the conductive absorbing composite material can be improved, and the resistance can be reduced.

[0133] By comparing Examples 1-2 and Comparative Example 2, it can be seen that the peeling force, resistance and magnetic permeability of the conductive absorbing composite materials provided by Examples 1-2 are better than those of Comparative Example 2, indicating that the present application uses a water-based slurry with specific components in combination with a coating, attachment and drying process to further improve the structural stability, electrical conductivity and absorption of the conductive absorbing composite material.

[0134] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a conductive wave-absorbing composite material, characterized in that: The conductive wave-absorbing composite material comprises a PET tape, a wave-absorbing layer and a conductive cloth which are stacked in sequence, and the preparation method comprises: The slurry for forming the absorbing layer is coated on the PET tape by a doctor blade coating method to form a slurry layer on the PET tape; the conductive cloth is attached to the slurry layer, dried, and the slurry layer is solidified to form the absorbing layer, thereby obtaining the conductive absorbing composite material; wherein, the slurry comprises, by weight: 100-200 parts of water, 60-90 parts of magnetic powder, 0.3-2 parts of dispersant, 0-3 parts of wetting agent, 0.1-2 parts of defoaming agent, 10-30 parts of binder, 0-20 parts of surface treatment agent, pH regulator and 5-30 parts of thickener.

2. The preparation method according to claim 1, characterized in that: The viscosity of the slurry is 4000-10000 Pa.s; Optionally, the conductive cloth is selected from copper conductive cloth.

3. The preparation method according to claim 2, characterized in that: During the scraper coating, the scraper has a height of 0.3-1 mm, a drying temperature of 45-200° C., and a drying time of 15-30 min.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The slurry comprises: 100-150 parts of water, 70-80 parts of magnetic powder, 0.3-1 parts of dispersant, 0.5-1 parts of wetting agent, 0.1-2 parts of defoaming agent, 15-20 parts of binder, 1-5 parts of surface treatment agent, pH regulator and 5-15 parts of thickener.

5. The preparation method according to claim 1, characterized in that: The slurry also includes 0.1-2 parts of an antiseptic and antifungal agent; Optionally, the preservative and mildew preventer is selected from at least one of isothiazolinones, phenylimidazoles, iodopropargyls or dithiocarbamates.

6. The preparation method according to claim 1, characterized in that: The magnetic powder is selected from at least one of nickel-zinc ferrite powder, zinc-manganese ferrite powder, iron-silicon-aluminum soft magnetic powder, iron-silicon-chromium soft magnetic powder, iron-nickel-molybdenum powder or carbonyl iron powder; Optionally, the magnetic powder is selected from at least one of sendustine-aluminum soft magnetic powder and iron-silicon-chromium soft magnetic powder.

7. The preparation method according to claim 1, characterized in that: The dispersant is selected from one of a cationic dispersant, a nonionic dispersant and a polymer dispersant; and / or, the wetting agent is selected from silicone-type wetting agents; And / or, the defoamer is selected from at least one of a mineral oil defoamer, a silicone defoamer, a lower alcohol defoamer or a lipid defoamer.

8. The preparation method according to claim 1, characterized in that: The binder is selected from at least one of polyurethane, acrylic acid or UV resin; And / or, the surface treatment agent is selected from one of polyvinyl pyrrolidone and γ-aminopropyltriethoxysilane; and / or, the thickener is selected from one of polyacrylate alkali swelling emulsion, polyurethane thickener, hydrophobically modified non-polyurethane thickener or inorganic thickener; And / or, the pH regulator adjusts the pH of the slurry to 8-9; optionally, the pH regulator is selected from ammonia water.

9. The preparation method according to claim 1, characterized in that: The preparation method of the slurry comprises: The weighed water and the magnetic powder are stirred evenly to wet the magnetic powder; The dispersant, the wetting agent, the defoaming agent, the binder, the surface treatment agent, the pH adjuster and the thickener are added in sequence and stirred to mix.

10. A conductive wave-absorbing composite material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Wave-absorbing material

    CN106190022A

  • Electromagnetic-shielding wave-absorbing film with selectable color

    CN203840697U

  • An electromagnetic shielding structure for flexible folding device

    CN209897545U

  • RADIO ABSORBING COATING

    RU2012142207A